Mobile Guide for Museum in Context of International Mountain Museum, Nepal (International Journal of Scientific Research and Management (IJSRM), 2022)
This paper aims to utilization of information technology at museum to provide the information about the museum and its artifacts properly in easier way with the help of digital devices such as mobile to the visitors.